Modern Approaches to the Diagnosis and Management of Dental Caries in Adult Patients (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2026)
Dental caries continues to be one of the most prevalent oral health problems among adult populations worldwide, significantly impacting masticatory function, esthetics, and overall quality of life. Modern approaches to the diagnosis and management of dental caries emphasize early detection, minimally invasive intervention, and individualized preventive strategies to halt disease progression and preserve natural tooth structure. This study examines contemporary diagnostic modalities, including digital radiography, laser fluorescence, and transillumination techniques, alongside restorative strategies such as adhesive resin composites, glass ionomer cements, and selective caries removal. The integration of patient-centered preventive care, risk assessment models, and evidence-based restorative protocols was evaluated in adult patients presenting with varying severity of carious lesions. Results demonstrate that early diagnosis, combined with conservative restorative and preventive measures, significantly reduces lesion progression, enhances patient comfort, and promotes long-term oral health sustainability. The study underscores the importance of adopting modern, technology-assisted approaches in clinical dentistry to improve therapeutic outcomes and optimize patient satisfaction. Dental caries remains a predominant oral health challenge among adults, leading to structural tooth damage, functional impairment, and diminished quality of life if not properly addressed. Modern clinical dentistry emphasizes early detection, minimally invasive restorative techniques, and individualized preventive strategies to halt disease progression and maintain dental integrity. This study investigates the application of advanced diagnostic tools, including digital radiography, laser fluorescence, and fiber-optic transillumination, in identifying incipient lesions in adult patients. Furthermore, it evaluates the clinical efficacy of contemporary restorative materials, such as adhesive composite resins and glass ionomer cements, in conjunction with selective caries removal and risk-based preventive interventions. Findings reveal that integration of these modern approaches facilitates preservation of healthy dental tissues, improves restoration longevity, reduces postoperative complications, and enhances patient satisfaction. The study underlines the importance of combining technological innovations with evidence-based protocols to optimize therapeutic outcomes and support sustainable oral health practices in adults.